PORTRAIT OF DISTANCE LEARNING FOR EARLY CHILDREN AGED 5-6 YEARS DURING THE COVID-19 PANDEMIC IN RA AL-MUAWANAH, CILANDAK BARAT - Tanenji, Tanenji (Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to identify and obtain portrait information on the online teaching and learning process at home during the Covid-19 pandemic. Group B or children aged 5-6 years. This research uses qualitative research with descriptive method. The data collection techniques used are observation, interviews and documentation techniques. The data in this study were obtained from observations of parents, school principals, teachers, and children as primary data and interviews with parents, school principals, teachers and children and documentation collection as secondary data. The steps used by the researcher in analyzing the data are the first pre-field stage, then the implementation of the research and finally concluding the data. The results showed that (1) In the planning and implementation process of online learning for early childhood at RA Al-Muawanah, Cilandak Barat Village, the planning made by the principal and teachers had gone well. However, the reality on the ground is when parents do not carry out optimally and become less effective learning. The online learning process is carried out through zoom and google duo by utilizing groups on whatsapp, (2) In the online learning process parents experience problems or obstacles first, problems related to the internet, second, problems related to parental involvement in the online learning process, third , problems related to the patience of parents in guiding children during online learning, fourth, problems related to the limitations of EDUCATIONAL LEARNING TOOLS, (3) The solution to overcome the problems of online learning is first, the school provides free quota facilities for parents who use personal quotas, second, the school provides understanding to parents to ask their children to study at the nearest teacher's house, third, parents can give rewards or praise for the efforts of their children who have done online learning, fourth, teachers can design EDUCATIONAL LEARNING TOOLS or educational games that are more varied and not monotonous when playing it.